Nieprzerwany żywot inkwizycji hiszpańskiej – studium przypadku z Estremadury (Politeja, 2020)
The Neverending Story of the Spanish Inquisition – a Study of a Case from ExtremaduraThe subject of this research is the book ‘El pecado nefando del obispo de Salamina’ (The deplorable sin of the bishop of Salamina) written in 2002 by the Spanish historian Francisco Núñez Roldán. In the context of post-memory I am interested in the origins of this book, which are connected with the Spanish Inquisition and the attempts to regard its author as a secondary witness. It is also important that the activities of the Holy Office (1478-1834) are not only the subject of continuing historical research but are also a rich source of inspiration for artists and scholars.